STRATEGI DIPLOMASI BUDAYA INDONESIA TERHADAP RUSIA DALAM KERANGKA KONSEP TTI (TRADE, TOURISM, & INVESTMENT) TAHUN 2016 - Ridwan, Katerina; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Globalization makes another point of national interest’s of a state. In this era, diplomacy is one of the other choices that often be used, called Soft Power Diplomacy. Indonesia chose to use cultural diplomacy as their way to gain the national interest. In fact, Indonesia is a country that has a culture as their powerful point. This research aim to explain about Indonesian cultural diplomacy’s strategy in TTI’s concepts as the framework in 2016.This research used qualitative research methods with descriptive explanation start from Indonesia-Russia’s relation in some sectors, TTI’s concepts as Indonesia-Russia’s prospect in case of coorperation , and cultural diplomacy’s strategic to Russia through Festival Indonesia in 2016. By means of implement diplomacy public’s theory, it can elaborate how Indonesia’s strategy to carry their interest in Russia with Indonesian Festival straight to TTI’s concepts.By seeing Russia as Indonesia’s strategic partner, the correct stimulus to their partnership for both countries are culture. In implementation, Indonesia and Russia through this Festival organizing cultural exhibition to represent their close emotional relation to each other as a country that has been built for a long time ago. Through this culture diplomacy’s strategy, Indonesia wants to reintrocude their state as potential business and investment’s state for Russia, also attract Russia’s tourist to increase their visit to Indonesia.Keyword : national interest, public diplomacy, culture diplomacy, TTI, tourism, Indonesia-Moscow Festiva